Comparative institutional analysis theory, corporations and East Asia : selected papers of Masahiko Aoki - Aoki, Masahiko (Edward Elgar E-Book Archive, 2013)
pt. I. Comparative mechanism design -- pt. II. The diversity of corporate governance : cooperative game approach -- pt. III. Analysis of the endogenous nature of institutions -- pt. IV. Institutions in East Asian economic development